International Baccalaureate (IB) program and students’ educational opportunities in Japan (Comparative & International Education Series, 2021)
This chapter draws on a qualitative study that examines how the promotion of International Baccalaureate (IB) education in Japan has contributed to increasing educational inequality in students’ gaining international experiences in the country.  With socioeconomic status (SES) and educational opportunities in a gap society of Japan as an analytical lens, this study attempts to delve into who has and/or will benefit from IB education in Japan.  It is identified that IB education provides students with international experiences within and outside of Japan.  IB diploma has created a pathway to postsecondary education outside of Japan.  However, its high cost has been one of the obstacles for some students to access the IB education along with students’ academic preparedness and schools’ geographical location.  This study provides implications for future research of how internationalizing education through global educational alternatives impacts on equity and social justice in education.